Umea Kultur. - Billgren, Ola; Björkman, Anders; Holmgren, Nils-Ake; Höste, Einar; Lundström, Peter; Pitch, Decay; Radström, Anna; Rolle; Von Rosen, Georg; Rydberg, Viktor; Sahlin, Lars; Sztulman, Paul; et al. (Umea : Umedalens skulpturpark, 1998)
Hietanen, Helena ; Cáven, Kari ; Cianakos, Cristos ; Cronqvist, Lena ; Persson, Roland ; Beaugrand, Catherine ; Pitch, Decay ; Billgren, Ola ; Lindstrand, Vicke ; Lindell, Lage ; Kirkeby, Per ; Höste, Einar
Umedalen Skulptur 98, Umedalens skulpturpark, Umea, 7.6. - 13.9.1998
Engels & Zweeds
kunstcatalogus